Application of EFQM Excellence Model to Persian Gulf Marine Passenger Terminal - Jafari, Hassan (Journal of Asian Business Strategy, 2013)
The present study is aim to assess the performance of the Persian Gulf Marine Passenger Terminal by using EFQM Excellence Model. The descriptive kind may seem the best appropriate frame for this study and it is conducted in all parts of the Persian Gulf Marine Passenger Terminal. For collecting the data we used the EFQM standard questionnaire. according to the 5 Enablers criteria in the such as: leadership, strategy and policy, people(stuff), resources and partnership, processes, and include 4 criteria in the resulted fields such as: customer results, people results, society results and key performance results. These criteria include 95 items with the 10-classed scale for regulation. This questionnaire distributed between among the 59 individuals of the terminal’s stuff for conducting the subjects’ statistics. Subjects were simply selected randomly from all units and parts of the terminals. the obtained results’ scores of the criteria contrasted to the standard score of the organizational Excellence model was detected 541.2 score from 1000 score and it mean 54.125 that is considered the pure achieved score and it has only 45.875 percent different distance to reach the Excellence situation. Therefore we can infer that Persian Gulf Marine Passenger Terminal is on its Excellence procedure.